Changes in Physical Activity Pre-, During and Post-lockdown COVID-19 Restrictions in New Zealand and the Explanatory Role of Daily Hassles - Hargreaves, Elaine A.; Lee, Craig; Jenkins, Matthew; Calverley, Jessica R.; Hodge, Ken; Houge Mackenzie, Susan (Frontiers in Psychology, 2021)
Covid-19 lockdown restrictions constitute a population-wide ‘life-change event’ disrupting normal daily routines. It was proposed that as a result of lockdown restrictions, physical activity levels would likely decline. However, it could also be argued that lifestyle disruption may result in the formation of increased physical activity habits. Using a longitudinal design, the purpose of this study was to investigate changes in physical activity of different intensities, across individuals who differed in activity levels prior to lockdown restrictions being imposed, and across three time periods: pre-, during- and post-lockdown. This study also examined the extent to which the experience of daily hassles explained any changes in physical activity. A convenience sample (N = 759) recruited through social media, provided data from an online survey administered during weeks 2-3 of a 5-week lockdown and 231 participants provided complete data again six weeks post-lockdown (72% female, M age = 43 years). Participants completed the International Physical Activity Questionnaire – Short Form and the Daily Hassles Scale. Results showed that vigorous and moderate intensity PA were significantly lower during- and post-lockdown compared to pre-lockdown in those individuals who had been highly active pre-lockdown. In contrast, for moderately active individuals pre-lockdown, vigorous and moderate intensity PA was significantly higher during-lockdown compared to pre-lockdown, and these increased levels of vigorous PA were maintained post-lockdown. Participants experienced daily hassles due to inner concerns, time pressures, family, and financial concerns to the same extent during- and post-lockdown. Those daily hassles had a small negative (Standardized β = -.11; p < 0.05) predictive effect on post-lockdown PA. It appears that to understand the effect of COVID-19 restrictions on PA, the activity status of individuals pre-lockdown needs to be taken into account. The daily hassles appeared to play a role in post-lockdown PA behaviour, but future research should investigate why these differences occur.